Cardiac iron metabolism during aging: role of inflammation and proteolysis - Walter, Sophia; Mertens, Christina; Muckenthaler, Martina; Ott, Christiane (Mechanisms of ageing and development, 2023)
Iron is the most abundant trace element in the human body. Since iron can switch between its 2-valent and 3-valent form it is essential in various physiological processes such as energy production, proliferation or DNA synthesis. Especially high metabolic organs such as the heart rely on iron-associated iron-sulfur and heme proteins. However, due to switches in iron oxidation state, iron overload exhibits high toxicity through formation of reactive oxygen species, underlining the importance of balanced iron levels. Growing evidence demonstrates disturbance of this balance during aging. While age-associated cardiovascular diseases are often related to iron deficiency, in physiological aging cardiac iron accumulates. To understand these changes, we focused on inflammation and proteolysis, two hallmarks of aging, and their role in iron metabolism. Via the IL-6-hepcidin axis, inflammation and iron status are strongly connected often resulting in anemia accompanied by infiltration of macrophages. This tight connection between anemia and inflammation highlights the importance of the macrophage iron metabolism during inflammation. Age-related decrease in proteolytic activity additionally affects iron balance due to impaired degradation of iron metabolism proteins. Therefore, this review accentuates alterations in iron metabolism during aging with regards to inflammation and proteolysis to draw attention to their implications and associations.